Textbook diagrams illustrating phases of the moon: Grade 10 learners' interpretation in relation to spatial ability - Mosoloane, Retselisitsoe Ananias (My University, 2013)
Many textbooks have diagrams illustrating astronomy concepts. However, research shows that sometimes learners struggle to obtain information illustrated in diagrams. This study investigated learners‘ ability to interpret diagrams illustrating phases of the Moon. Three constructs formed a theoretical framework used to design the study and interpret results: a theory associated with design and interpretation of diagrams, spatial ability theory which explains how people mentally manipulate objects in space, and the theory of models which proposes issues to take into consideration when using models (e.g. diagrams) in classrooms. I collected and processed data in three phases. In the first phase, I administered a diagnostic test to 75 learners, investigating their ideas about concepts associated with phases of the Moon. In addition, I administered six spatial ability tests to these learners, investigating their mastery of spatial ability skills needed to understand concepts associated with phases of the Moon. Results show that all the learners lacked background knowledge of these concepts. Furthermore, most of the learners lacked spatial ability skills needed to understand these concepts. I used these results to select 10 learners for participation in the third phase of the study. Five of these learners had high spatial ability skills while the other five had low spatial ability skills. During the second phase of the study, I analyzed 28 diagrams illustrating phases of the Moon to investigate the extent to which their composition (i) might enable learners to perceive all diagrammatic information, (ii) might enable learners to understand information for which the diagrams are intended, and (iii) complies with context of intended learners. Results show that only few diagrams were designed in a way that might hinder perception of information. However, most diagrams were designed in a way that might hinder understanding of intended information, and many did not comply with context of intended viewers. These results enabled me to select four diagrams having the fewest design problems to be used in the third phase of the study. In the third phase, I interviewed the ten learners selected during the first phase, to investigate their ability to interpret diagrams illustrating phases of the Moon. The learners were generally able to interpret aspects of diagrams which required the diagrams to be perceived in two-dimensional space. However, they struggled to interpret aspects of the diagrams which required perception and mental manipulation of the components of the Earth-Moon-Sun system in three-dimensional space. The high spatial-ability learners were better able to cope with tasks requiring mental manipulation of the Earth-Moon-Sun system in space than their low spatial ability counterparts. These results suggest the existence of a link between spatial ability and learners‘ interpretation of these diagrams. Teachers should be informed about these findings to help them understand how usage of the diagrams might hinder leaning. This information might help them use diagrams that have fewer design problems. Also, teacher trainers should be informed about these findings, to help them caution pre-service teachers about problems found in textbook diagrams. In addition, publishers should be informed about findings of this study to help them improve quality of diagrams in school textbooks. Furthermore, researchers should investigate strategies that can help learners (particularly those with low spatial ability skills) to better cope with aspects of diagrams which require mental manipulation of the Earth-Sun-Moon system in space. Keywords Astronomy, phases of the Moon, diagram design, diagram interpretation, spatial ability.
Keywords: Moon - Handbooks, manuals.; Illustration of books.; Astronomy - Chart, diagrams, etc.